2017
DOI: 10.1111/apt.14261
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends, clinical patterns and outcomes of NAFLD‐related HCC in patients undergoing liver resection over a 20‐year period

Abstract: Non-alcoholic fatty liver disease increased substantially over the past 20 years among resectable HCCs. It is now the leading cause of HCC occuring without/or with only minimal fibrosis. NAFLD patients are older, with larger tumours while survival and recurrence rates are as severe as in other aetiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 28 publications
9
82
1
Order By: Relevance
“…In fact, the majority of NASH patients with HCC die from their primary liver cancer rather than from cardiovascular disease, and rates of HCC‐related mortality are greatest in the NASH population . On the other hand, survival rates for surgical resection in patients with NASH and HCC are similar to other liver diseases, particularly in the absence of cirrhosis, albeit in highly selected surgical candidates …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the majority of NASH patients with HCC die from their primary liver cancer rather than from cardiovascular disease, and rates of HCC‐related mortality are greatest in the NASH population . On the other hand, survival rates for surgical resection in patients with NASH and HCC are similar to other liver diseases, particularly in the absence of cirrhosis, albeit in highly selected surgical candidates …”
Section: Discussionmentioning
confidence: 99%
“…The Japanese NOBLESSE study group found that this more than doubled from 10% in 1991 to 24.1% in 2010 . While HCC often arises in the presence of cirrhosis (with an exception being chronic hepatitis B given the direct hepatotoxic nature of the virus), NASH‐associated HCC may develop in both the presence and absence of cirrhosis . For this reason, there may be a substantial number of higher risk patients who are not captured by routine HCC screening per current guidelines from the American Association for the Study of Liver Diseases (AASLD) …”
Section: Introductionmentioning
confidence: 99%
“…The development of HCC in a non‐cirrhotic setting has long been recognised as an uncommon event in patients with chronic liver disease, occurring primarily in the setting of hepatitis B virus (HBV) infection . Accumulating data from different case reports and studies over the past two decades have shown that the same phenomenon occurs in the setting of non‐cirrhotic NAFLD . The mechanisms of carcinogenesis in the setting of non‐cirrhotic NAFLD are not entirely clear, but the chronic inflammatory state associated with obesity and commonly seen with NAFLD, insulin resistance and lipotoxicity may alter hepatocyte proliferation and different modes of hepatocyte death, thus promoting a carcinogenic milieu …”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, a study from France reported that the prevalence of NAFLD in patients with HCC increased from 2.6% (1995) to 19.5% (2014). 14 In a retrospective study of liver transplant (LT) recipients in the United States from 2002 to 2012, NASH was noted to be the second leading etiology of HCC-related liver transplantation, 15 whereas other similarly designed studies also have shown or projected the presence of an increasing trend. 2,[16][17][18][19][20] All this is accompanied by an alarming conundrum in the field of NAFLD and NASH: despite rapid growth in the burden of the disease, there are no validated diagnostic or prognostic noninvasive biomarkers for NASH and related fibrosis, and there are no effective pharmacologic therapies with proven efficacy and safety.…”
mentioning
confidence: 99%